2017
DOI: 10.1186/s12879-017-2496-4
|View full text |Cite
|
Sign up to set email alerts
|

Joint Bayesian modeling of time to malaria and mosquito abundance in Ethiopia

Abstract: BackgroundThis paper studies the effect of mosquito abundance and malaria incidence in the last 3 weeks, and their interaction, on the hazard of time to malaria in a previously studied cohort of children in Ethiopia.MethodsWe model the mosquito abundance and time to malaria data jointly in a Bayesian framework.ResultsWe found that the interaction of mosquito abundance and incidence plays a prominent role on malaria risk. We quantify and compare relative risks of various factors, and determine the predominant r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Climatic variables like temperature and precipitation in uenced malaria proportion in both landscapes. This result does not come as a surprise, as the in uences of temperature and precipitation on malaria are well established for the area [19,22,23]. Our study shows that in a geographically diverse area like the Amhara region, climatic variables can vary greatly within woredas and drive sub-woreda level malaria proportion.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Climatic variables like temperature and precipitation in uenced malaria proportion in both landscapes. This result does not come as a surprise, as the in uences of temperature and precipitation on malaria are well established for the area [19,22,23]. Our study shows that in a geographically diverse area like the Amhara region, climatic variables can vary greatly within woredas and drive sub-woreda level malaria proportion.…”
Section: Discussionsupporting
confidence: 62%
“…These ndings are in contrast to the general expectation of relationships between malaria cases and temporary water bodies. Other studies from different parts of Ethiopia have found that woredas with high wetlands cover had high malaria incidence [24] and distance to breeding sites for samples of individual households in uences malaria risk on household level [23,67,68]. However, those previous studies have been performed at different spatial scales, and the proximity of temporary water bodies was much less important at the kebele level within he woredas that we studied.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Dalian export-oriented economy is highlighted [5], and there is a great demand on the international freight market potentials. During the period of twelfth five, the demand of international air freight is over 300,000 tons.…”
Section: Export-oriented Economy Brought Better Development Opportunimentioning
confidence: 99%
“…Thus, remote sensing is a useful tool for studying the effects of environmental conditions on mosquito borne diseases like malaria [ 24 , 32 35 ]. In Ethiopia, such studies have established relationships between malaria risk and remotely-sensed environmental factors, such as land surface temperature [ 33 , 36 , 37 ], precipitation [ 36 , 38 ], greenness and moisture indices [ 33 ], wetland cover [ 27 ], and distance to water bodies [ 36 ].…”
Section: Introductionmentioning
confidence: 99%